A Deed to the Light - Walker, Jeanne Murray (Book collections on Project MUSE., 2004)
In A Deed To the Light Jeanne Murray Walker asks probing questions about the depth of grief, about letting go, and about the possibility of faith. Her poems have been described by John Taylor, writing in Poetry, as "splendid, subtly erudite, uplifting, and funny." _x000B_